Identification of Primary Metabolite Profiles Reveals Quality Characteristics of Citrus maxima ‘Shatian Yu’ from Different Origins - Yujiao Peng; Meixin Li; Fangfei Song; Shuilan Liu; Yuxiang Qin; Baoqing Hu; Xueyu Cui (Current Issues in Molecular Biology)
Citrus maxima ‘Shatian Yu’ displays varying nutritional profiles influenced by its production area. This study evaluated pomelo fruits from four primary and one developing ‘Shatian Yu’ production area. Notably, ‘Shatian Yu’ from the Guilin area exhibited higher sugar and alcohol content, suggesting enhanced taste. Principal component analysis and OPLS-DA revealed significant metabolite differences among production areas. In Guilin, variations were observed in a few substances, including sugars, alcohols, and phenolic acids. When compared with Rong City, Guilin showed a decrease in four phenolic acids and an increase in three organic acids, eighteen amino acids, eighteen lipids, and one vitamin. This comprehensive analysis provides valuable insights for the development of ‘Shatian Yu’ cultivation, highlighting the impact of production areas on fruit quality.